A CRISPR Interference System for Efficient and Rapid Gene Knockdown in Caulobacter crescentus - Guzzo, Mathilde (mBio, 2020)
CRISPR interference (CRISPRi) is a powerful new tool used in different organisms that provides a fast, specific, and reliable way to knock down gene expression. Caulobacter crescentus is a well-studied model bacterium, and although a variety of genetic tools have been developed, it currently takes several weeks to delete or deplete individual genes, which significantly limits genetic studies. Here, we optimized a CRISPRi approach to specifically downregulate the expression of genes in C. crescentus. Although the Streptococcus pyogenes CRISPRi system commonly used in other organisms does not work efficiently in Caulobacter, we demonstrate that a catalytically dead version of Cas9 (dCas9) derived from the type II CRISPR3 module of Streptococcus thermophilus or from Streptococcus pasteurianus can each be effectively used in Caulobacter. We show that these CRISPRi systems can be used to rapidly and inducibly deplete ctrA or gcrA, two essential well-studied genes in Caulobacter, in either asynchronous or synchronized populations of cells. Additionally, we demonstrate the ability to multiplex CRISPRi-based gene knockdowns, opening new possibilities for systematic genetic interaction studies in Caulobacter.